A (re)produção do espaço do Maciço de Baturité: análise das políticas de desenvolvimento urbano-regiona - Nascimento, Alexandre Sabino do (2008)
The current modifications observed in Performance‘s Model of the State of Ceará at Public Politics for the regional- urban development, since from middles of the eighties, especially in Solid of Baturité-CE, causes the present researche. It also points the process of (re)production in area, , coming of competitive integration in the cities ‗ market in search os global surplus value and of ―incomes monopolists‖ of the Tourist activity, mainly in the highland sub-area of the Solid area. It understands itself that studying the process of production at Urban Space-regional, of study‘s area, it can be understood the spaces practices on present and in matter stimulated them by the State. It realizes this process as a need of the Capitalism for its development and maintenance with the continuous production of the space transformed in merchandise. For the performance‘s analysis , were taken it reference some programs and regional development plans done by the State in different administration scales. For us to arrive to the objectives of the research , we will use this return to the pas, proposed in the method , but being evidenced that the study seeks the present, being the necessary historical study for understanding of the process, for us we won‘t fall in the trap of a simple historical analysis. The research starts about the qualitative and quantitative data analysis, doing a little use of statistical techniques , it was analyzes the phenomena described in the documental collection, by the bibliographical research , and confronted them with the direct observation of the atmosphere, stage of the research – municipal districts of the sub-highland area of the Solid of Baturité. So, get difficult with the mentioned problems, we locate a positive performance or solid with concretes results of the planning, because all of the areas mentioned as priority at programs and development projects for the area, pass for structural problems. It stands out, like this, the lack of a larger performance in public politics as the ones that works with the offer services and equipments of buses consumption buses, that in a touristic region, before they serve tourists , are indispensable for the local population.